[Where do we go from here ; Shattered dreams ; The Boys of the Little League [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
The lowland Pinatubo dwellers being transported to the evaluation camps. Investigates their social conditions in the camps. Interview with overseas contract workers about their social conditions especially their pitfalls. Interview with Philippine players to the Little League in Pennsylvania. The players have been stripped of its championship on the bases of reports that the team violated player eligibility requirements.
Where do we go from her (10 min.) -- Shattered dreams (18 min.) -- The Boys of the Little League (12 min.)
VHS.
Keywords: Disaster victims -- Pinatubo, Mount (Zambales); Basketball players -- Philippines; Filipinos -- Employment -- Middle East countries; Filipinos -- Social conditions